A Review Article of the Pragmatics Competence in EFL Learning Context - Amaliah, Amaliah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Cross-cultural communication requires pragmatics. Pragmatics is "the ability to use language appropriately in social settings." Pragmatic competence in another language involves understanding and carrying out communicative activities or speaking and using the language effectively in varied situations. Several relevant literature and library sources were used for this research. According to Kasper et al. "Library research, like its twin, the academic experiment, involves a kind of organized investigation with prescribed instruments, rules, and tactics." Three core library research systems are examined: checking reference sources and databases, finding and utilizing information sources, and assessing information sources according to research objectives. This article analyzes data on pragmatic competence in students of Indonesian and other foreign languages. The author used a public digital search engine to examine scientific literature on pragmatic competency studies in Indonesia to correlate disparate data and find appropriate results. Qualitative research may be more comprehensive. This study found that most studies used a descriptive qualitative approach. The exam is detailed. Most studies used a qualitative approach to characterize L2 practical skills by level and test, while one study assessed learners' cross-cultural awareness during encounters. Most studies on educational participation and the impact of cross-cultural awareness on pragmatic knowledge in EFL learning use qualitative methods, although there are three studies that use quantitative methods. Reviews and debates provide suggestions. Recent research on pragmatic competence in EFL learning settings features a descriptive qualitative approach complemented by Creswell's qualitative approach that provides greater detail about the phenomenon, and all three studies use quantitative methodology. Pragmatic competence improves EFL students' social skills. Al Khadhmi found that the pragmatic meaning of situational utterances was more difficult to interpret compared to lexical stimuli. Therefore, it is better to continuously improve certain areas, such as training EFL students' awareness before they understand a foreign language and activating pragmatic competence and pragmatic components in them, as this affects their communication inside and outside the classroom